PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KOMITMEN ORGANISASI TERHADAP SENJANGAN ANGGARAN - Nurma Risa (JRAK: Journal of Accounting Research and Computerized Accounting, 2014)
The purposes of this study are to prove that budgeting participation and organization commitment can influencethe budget lack at UNISMA Bekasi. Using structural equation model (SEM) method, with Partial Least SquarePath Modelling, this study prove that budgeting participans are tend to do budget lack. On the other hand, a person with high commitment to organization is tend to minimize budget lack and will do everything to achiveorganization goals.